Prevalence of Salmonella and Escherichia coli contamination in shrimp (Penaeus monodon) farms, depots and processing plants in different areas of Bangladesh (Asian Journal of Medical and Biological Research, 2016)
A study was conducted to determine the level of contamination by indicator organisms (Salmonella and Escherichia coli) in shrimp (Penaeus monodon) farms, depots and processing plants of Coxs Bazar, Khulna, Bagerhat and Satkhira districts of Bangladesh using conventional technique of bacterial isolation and identification. The results of this study revealed that prevalence of Salmonella positive samples was 43.7%, 62.5%, 20% and 0.0% for water, pond scum, shrimp and basket samples, respectively at farm level. Meanwhile, the prevalence of E. coli positive samples was 62.5%, 43.7%, 60% and 60% for water, pond scum, shrimp and basket samples, respectively at farm level. In case of depots, shrimp, basket and mat samples were analyzed and found 20%, 56.3% and 23% positive for Salmonella and 53.3%, 37.5% and 92.3% positive for E. coli. Bacteriological assessment of the shrimp samples obtained from four seafood processing plants revealed that all the samples were found contaminated with Salmonella and E. coli except the samples of one industry. Investigation finally showed that with few exceptions all the samples from farms, depots and processing plants have different levels of contamination by Salmonella and E. coli, which is very much alarming for shrimp industry of Bangladesh.Asian J. Med. Biol. Res. June 2016, 2(2): 171-176